2021
DOI: 10.1038/s41598-021-81055-4
|View full text |Cite
|
Sign up to set email alerts
|

Lattice thermal transport in two-dimensional alloys and fractal heterostructures

Abstract: Engineering thermal transport in two dimensional materials, alloys and heterostructures is critical for the design of next-generation flexible optoelectronic and energy harvesting devices. Direct experimental characterization of lattice thermal conductivity in these ultra-thin systems is challenging and the impact of dopant atoms and hetero-phase interfaces, introduced unintentionally during synthesis or as part of deliberate material design, on thermal transport properties is not understood. Here, we use non-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Consequently, the phonon thermal conductance shows lower values. Such localization in thermal transport has also been studied in asymmetric harmonic chains 35 and observed in 2D fractal heterostructures 47 , 48 , which leads to a very large reduction in the thermal conductivity.…”
Section: Resultsmentioning
confidence: 91%
“…Consequently, the phonon thermal conductance shows lower values. Such localization in thermal transport has also been studied in asymmetric harmonic chains 35 and observed in 2D fractal heterostructures 47 , 48 , which leads to a very large reduction in the thermal conductivity.…”
Section: Resultsmentioning
confidence: 91%
“…For the higher generation SPGs, we get more localized phonon modes which we confirm by studying the phonon transport up to the 8th generation SPG (not shown here). Such localization of phonon modes has also been studied in asymmetric harmonic chains 35 and observed in 2D fractal heterostructures 44,45 . The corresponding phonon thermal conductance k ph as a function of temperature is shown in Fig.…”
Section: Thermoelectric Propertiesmentioning
confidence: 94%
“…These as-fabricated defects can be introduced during sample preparation (e.g., grain boundaries or isolated vacancies and antisite defects) or transfer (e.g., wrinkles and tears) 8 . Previous studies have shown that defects can be used to tune properties [9][10][11][12] , control strain 8 , and induce moiré patterns in 2D transition metal dichalcogenides 13,14 . However, more work is needed to understand the relationship between intrinsic defects, SAWs, and key material properties.…”
Section: Introductionmentioning
confidence: 99%